FAKTOR-FAKTOR PENYEBAB TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK - Subrahmaniam Saitya, Ida Bagus (Institut Hindu Dharma Negeri Denpasar, 2019)
Law No. 23 of 2002 concerning Child Protection, affirms that children are a mandate as well as the gift of God the Almighty, which we must always guard because in them the dignity, dignity and rights as human beings must be upheld. Children who are victims of crime are weak people who often cannot protect and help themselves because of their situation and conditions. Crime of sexual violence against children is a crime that uses violence or threats of violenceagainst children so that the child can be controlled for sexual relations. Internal factors causing criminal acts of sexual violence such as the proximity of the perpetrator to the victim, the role of the perpetrator, and the position of the victim. External factors that cause sexual violence crimes, namely environmental influences, such as being far from the crowd, lonely, or closed places that allow perpetrators to commit sexual violence.